An evaluation of the northern integrated supply project: feasibility of filling glade reservoir - Dudziak, Kelsey, author; Kimbrell, Clint, author; Colorado State University, publisher (Colorado State University. Libraries, 2015)
The Northern Integrated Supply Project (NISP) aims to develop much needed water storage along the Front Range of Colorado. A primary component of this effort is the construction of Glade Reservoir, which has a proposed capacity of 170,000 acre-feet and an estimated annual yield of 40,000 acre-feet. Water allocation in Colorado is governed by the Doctrine of Prior Appropriation, which requires that all historical water users receive their decreed streamflow water right before any water can be diverted by new water users. NISP intends to fill Glade Reservoir with excess streamflows from the Cache la Poudre River, which refers to streamflow that has not yet been allocated to senior water users. The MODSIM River Basin Management Decision Support System developed at Colorado State University is applied to simulating the filling of Glade Reservoir using historic streamflow and diversion data for the past 50 years to determine if this project is capable of required water deliveries of the project for satisfying the projected demand. Several additional simulations were executed in MODSIM in which the reservoir size and annual yield were altered in order to provide decision-makers with additional options regarding the construction of this storage project.
Hydrology days 2015
AGU hydrology days 2015
2015 annual AGU hydrology days was held at Colorado State University on March 23 - March 25, 2015.